Relatia se mai poate scrie [tex] ab^{2} [/tex]-[tex] bc^{2} [/tex]=abc
[tex] ab^{2} [/tex]100a+bc·(bc+1)
U([tex] ab^{2} [/tex])={0; 1; 4; 5; 6; 9} , U(100a+bc(bc+1))={0; 2; 6} si b[tex] \neq [/tex]0⇒b{4; 6}
b=4⇒[tex] a4^{2} [/tex]=100a+[tex] 4c^{2} [/tex]+4c
a=2⇒c∈{2; 7}
a=5⇒U([tex] 4c^{2} [/tex]+4c)[tex] \neq [/tex]5
a=6⇒[tex] 64^{2} [/tex]>900+[tex] 49^{2} [/tex]+49
b=6⇒[tex] a6^{2} [/tex]=100a+[tex] 6c^{2} [/tex]+6c
a=6⇒c∈{2; 7} si [tex] 66^{2} [/tex][tex] \neq [/tex]500+6c·(6c+1)
a=7⇒[tex] 76^{2} [/tex]>900+[tex] 69^{2} [/tex]+69⇒nu se verifica relatia
~Sper ca te-am ajutat!~